Control Strategy for Power Sharing in Input-Parallel and Output-Parallel Connected DC-DC Converters - Negar Amoozadeh; Vahid Abbasi (AUT Journal of Electrical Engineering, 2023)
Input-Parallel Output-Parallel DC-DC converters are convenient for high voltage and high current applications. One important goal of this type connection is to power-share and reduce circulating current between the converters. Therefore, control methods for power-sharing between converters should be used when the parameters mismatch. In this paper, a configuration comprising two DC-DC common grounded Z-source converters with Input-Parallel Output-Parallel connections is presented, which common grounded Z-source converter have advantages over similar converters. This study proposes two control strategies: (1) a decentralized inverse-droop control, (2) a general control strategy. Inverse-droop control is a simple method and does not need any communication between parallel converters. In the general control strategy, each converter is self-contained, and no external controller is required for achieving input/ Output Current Sharing, and a few wires are needed to create the entire system. The simulation results of an Input-Parallel Output-Parallel system comprising two common grounded Z-source converters are evaluated for investigating effectiveness of general control and inverse-droop control. It reported performance of the general control method to be better than the decentralized inverse-droop control method, which enhances the stability and dynamic characteristics of the system. The validity of the two control strategies has been studied through MATLAB simulation and the results were satisfactory.